DETERMINAN RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG LISTING DI BEI - Laung Andri Pranata Siregar; Meutia Dewi; Ismanidar, Nur (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study aims to determine the effect of Debt to Equity Ratio (DER), Return on Asset (ROA), and Earning Per Share (EPS) on Stock Return in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2013-2017. The population in this study is all Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2013-2017, amounting to 18 companies. The sample in this study amounted to 8 companies taken using purpose sampling method. The data analysis method used is multiple linear regression and hypothesis testing using SPSS as the analysis tool. The results of research are Debt to Equity Ratio (DER) has a negative effect on stock return, while Return on Asset (ROA) and Earning Per Share (EPS) have a positive effect on stock return. The coefficient of determination results show that the Debt to Equity Ratio (DER), Return On Asset (ROA), and Earning Per Share (EPS) variables contribute or influence stock return by 6.0%.The results of the partial study (t-test) show that the Debt to Equity Ratio (DER), Return On Asset (ROA), and Earning Per Share (EPS) variables have an insignificant effect on stock return (tsig > 0.05). Based on simultaneous testing (F-test), it is shown that the Debt to Equity Ratio (DER), Return on Asset (ROA), and Earning Per Share (EPS) variables have an insignificant effect on stock return (Fsig > 0.05).